Clinical outcomes in pediatric tibial lengthening and deformity correction: A comparison of the Taylor Spatial Frame with the Orthex Hexapod System. (April 2021) - Messner, Juergen; Chhina, Harpreet; Davidson, Sophia; Abad, Jero; Cooper, Anthony
Abstract: Purpose: Comparison of two hexapod frame systems in paediatric tibial deformity correction; the Taylor Spatial Frame (TSF) and Orthex Hexapod System. Methods: Paediatric patients with congenital and acquired tibial deformities treated with either TSF (between 2014 and 2016) or Orthex (between 2017 and 2019) frames were included in a retrospective comparative study. Outcome measures were healing index, pin infection rate, regenerate quality and density, software residual rate, deformity correction accuracy, strut exchanges and quality of life (QoL). Results: The TSF group had 17 patients (18 frames) and the Orthex group had 21 patients (25 frames). The most common indications for tibial deformity correction were fibular hemimelia (14) and septic or traumatic growth arrest (8). The median time in frame was 230 days (TSF) versus 203 days (Orthex) (p= 0.06). The mean lengthening achieved was 54 mm (TSF) and 51 mm (Orthex) (p = 0.41). The healing index was 41 days/cm (TSF) versus 43 days/cm (Orthex) (p = 0.70). Pin site infections occurred more in the TSF cohort (40%) than in the Orthex cohort (18%) (p < 0.001). The regenerate in the Orthex group showed higher density at three months (p = 0.029) and was more homogenous (p = 0.023) at six months after frame application. Strut exchanges were less frequent with the Orthex system (p < 0.0001). QoL measures were similar in both cohorts (p = 0.92). Conclusions: This is the first study to compare two hexapod designs in paediatric orthopaedics. The Orthex system showed superiority in regenerate quality and a significant reduction in pin site infection rates. Both systems delivered predictable and accurate limb deformity correction. Level of evidence: III